The diversity of Trichinella in natural habitats of the Russian Far East - Odoyevskaya, Irina M.; Seryodkin, Ivan V.; Spiridonov, Sergei E. (Russian Journal of Nematology, 2018)
The juveniles of Trichinella nematodes were collected from the muscular tissue of different predaceous mammals in the natural habitats of the Russian Far East (Primorsky Region of the Russian Federation). Identification of Trichinella nematodes up to the species level was based on the analysis of nucleotide sequences of mitochondrial DNA. The amplified sequence contained CoxI gene and adjacent tRNA sequences. Three species of trichinellids were detected in the studied material: T. spiralis, T. pseudospiralis and T. nativa. The latter species demonstrated the strongest genetical diversity as five haplotypes of T. nativa were discovered in the studied material. New hosts were reported for Trichinella nematodes in the Russian Far East including a leopard cat (Prionailurus bengalensis). Other mammal hosts included an Asian badger (Meles leucurus), a brown bear (Ursus arctos), a lynx (Lynx lynx), a red fox (Vulpes vulpes) and a sable (Martes zibellina).